In the past the future used to be much brighter: embodied austerity in Portugal - Lima, A. P. (2018)
Recent trends have put conflicts around human rights in the centre of anthropological theoretical challenges. Human rights, for its close association with universalism, constitutes a challenge to anthropological approaches due to their intrinsic intellectual commitment to relativism. In a world of blurred frontiers, however, this imperative to understand the local in its own terms may come at odds with another fundamental commitment of a moral nature – the endorsement of “human rights” in its universality. This constitutes what may be called “the moral dilemma of relativism”. This panel approaches relations between suffering, morality, and human rights. It aims to contribute to the discussion of relativism and morality through the discussion of the interlinkage between macrolevel phenomena, such as state economic policies, mainstream medical discourses and political processes of social rights reductions, and the production of particular forms of suffering. It is composed of three papers which intend to contribute, through data from specific ethnographic contexts, to the deepening of understanding of this paradox and its consequences for anthropological theory. The papers deal with: a) austerity policies, personhood and the management of crisis; b) “obstetric violence”, “the humanization of birth” and the ambiguities of the status of medical discourses; c) the process of social rights reduction, and the increase of intolerance and violence into the gender and sexuality fields.